Team-to-team transmission of COVID-19 in ice hockey games - a case series of players in Finnish ice hockey leagues - Kuitunen, I.; Uimonen, M. M.; Ponkilainen, V. T. (Infectious Diseases, 2021)
Background: The COVID-19 pandemic suspended nearly all team sports globally. The pro series have resumed playing by creating safe bubbles or massive testing protocols. Amateur level sports have also restarted seasons without possibility for such precautions. Our aim was to report the epidemiology of COVID-19 in an amateur ice hockey team and the team-to-team transmission during two games.